The aeronautical group in Kyiv polytechnic institute (1908-1915) - Tatarchuk, V. V. (History of science and technology, 2014)
In this article the history of one of the first aviation organization in Ukraine − the aeronautical group in Kyiv Polytechnic Institute − is presented. The research is based on the archive sources and newspaper’s chronicles. A circumstances, scale and sizes of the work of the students have been described. The new archive materials are introduced into scientific circulation, which were unknown for the researches before.